(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
Drying technology is one method of preserving eggs by converting them into egg yolk powder. This study aims to analyze the physicochemical, microbiological and organoleptic characteristics of cookies made with egg yolk powder formulation over storage periods of 0, 15, and 30 days. The experimental design used a single factor of storage duration (0, 15, and 30 days) with analysis of variance (ANOVA) to determine the effect of storage time with a 95% confidence interval. Cookies with egg yolk powder formulation showed changes in both physicochemical (pH, Aw, water content and texture) and microbiological values during the storage period. There was an increase in water activity and water content of the cookies, while a decrease was observed in pH and breaking strength. The microbiological changes in the cookies still met the Indonesian National Standard (SNI) for cookies up to day 30 of storage. The organoleptic test results indicated that cookies with egg yolk powder formulation were generally well-received, with characteristics of color, aroma, texture, and taste falling within the range of like to favorably liked.